Educational software: Alternative resources for Building thinking in the classroom (Research, Society and Development, 2024)
Currently, the computer represents an essential tool in companies and schools, as a means of information, communication, knowledge production and, mainly, work. The school begins to modernize itself, seeking to be in tune with the emergence of new technologies that are in force. It cannot be left out of technological progress, lest it run the risk of becoming outdated for future generations. The computer is a resource in the teaching and learning process, which favors the construction of a more attractive curriculum for students, aiming to facilitate the construction of learners' knowledge. The present study aims to highlight the importance of software as alternative resources in the construction of thinking in the classroom. Therefore, the following question is presented: - what is the role of software in education and how do they work in the classroom? The methodology is based on a bibliographical review, whose theoretical framework consists mainly of the thinking of several authors with vast knowledge on the subject in question. In short, it is believed that educational software facilitates, both the formation and construction of knowledge and the act of thinking of students in the classroom, as an enriching means of teaching-learning.